1990
DOI: 10.1115/1.2927684
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Heat Transfer and Film Cooling on Low Aspect Ratio Turbine Nozzles

Abstract: The effects of the three-dimensional flow field on the heat transfer and the film cooling on the endwall, suction, and pressure surface of an airfoil were studied using a low speed, fully annular, low aspect h/c = 0.5 vane cascade. The predominant effects on the horseshoe vortex, secondary flow, and nozzle wake of increases in the heat transfer and decreases in the film cooling on the suction vane surface and the endwall were clearly demonstrated. In addition, it was demonstrated that secondary flow has little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Equation [8] Where, = uncertainty Equation [9] Equation [10] Equation [11] Combining equation [2][3][4][5] Hence, the total uncertainty (Instrument accuracy + uncertainty due to unsteadiness of total pressure) can be given as, …”
Section: Applying Kline and Mcclintock's [24] Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation [8] Where, = uncertainty Equation [9] Equation [10] Equation [11] Combining equation [2][3][4][5] Hence, the total uncertainty (Instrument accuracy + uncertainty due to unsteadiness of total pressure) can be given as, …”
Section: Applying Kline and Mcclintock's [24] Methodsmentioning
confidence: 99%
“…In the coming years, studies were conducted by Sjolander [6], Langston [7] and many more, which were finally summarized by Sieverding [8] in his comprehensive review paper. These were further followed by Sharma and Butler [9], Goldstein and Spores [10], Takeishi et al [11]. Blanco et al [14] also looked into the effects of a backward and forward facing step with and without leakage flow and found that the forward facing step produced stronger endwall flows compared to the backward facing step.…”
Section: Secondary Flow Physicsmentioning
confidence: 99%
“…These vortices are shown in Figure 3.3, which illustrates the secondary flow model of Takeishi et al (1990). There are many secondary flow models, but they do not all agree on the existence of the smaller corner vortices (Goldstein and Spores (1988)) and the path that the suction leg of the horseshoe vortex follows.…”
Section: Passage Vorticesmentioning
confidence: 99%
“…3.1 Structure of supersonic trailing edge shock system (Denton and Xu (1989)). 18 3.2 Schematic illustration of the development of secondary flow in a rotor blade passage (Lakshminarayana (1996) Takeishi et al (1990) …”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Opt 2 leads to more crossflow to the hub than the baseline design, and thus it suppresses the secondary flow vortices in the hub side. Based on experimental (24) and LES results (25) , it has been reported that the secondary flow vortices originate in horseshoe vortices caused by the flow interference between the blade leading edge and end walls, which then leads to total pressure loss. Based on these reports, blade shapes were examined as follows.…”
Section: Journal Of Computational Science and Technologymentioning
confidence: 99%